2021
DOI: 10.1021/acs.joc.1c00369
|View full text |Cite
|
Sign up to set email alerts
|

Diisoprenyl-cyclohexene/ane-Type Meroterpenoids from Biscogniauxia sp. and Their Anti-inflammatory Activities

Abstract: A secondary metabolites investigation on Biscogniauxia sp. 71-10-1-1 was carried out, which led to the obtention of nine new diisoprenyl-cyclohexene/ane-type meroterpenoids (1–9) and two new isoprenylbenzoic acid-type meroterpeniods (10–11). The structures of these isolates were established on the basis of multispectroscopic analyses, ECD, and 13C chemical shifts calculations, and single-crystal X-ray diffraction. Among them, biscognin A (1) is the first diisoprenyl-cyclohexene-type meroterpenoid with a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…These skeletons include 14 monocyclics (cyclohexene/ ane, e.g., iso-A82775C 40 ), 62 bicyclics {benzofuran (6/5, e.g., truncateols D−L 43 ), chromen (6/6, e.g., oxirapentyns F−J 31 ), naphthalene (6/6, biscognin B 44 ), and spiro[cyclohexene/anecyclopropane] (6/3, pestalotriols A and B 45 )}, 18 tricyclics {furo[2,3-g/h]chromene (5/6/6, e.g. pestalotheols A, B, and D 46 ), pyrano[2,3-g]chromene (6/6/6, oxirapentyn K 31 ), chromene−cyclocarbonate fused (6/6/5, biscognienyne F and felinoid A 30,44 ), cyclopropa[c]benzofuran (3/5/6, biscognienyne E 44 ), spiro[chromene-cyclopropane] (6/6/3, pestaloficiols B−E 47 ), and spiro[cyclopropane-naphthalene] (3/6/6, biscognin A 44 )}, and one tetracyclic {cyclopropa [3,4]furo[2,3h]chromene, 3/5/6/6, pestaloficiol A 47 }. In this study, four new members (1−4) with two distinct types of 6/6/6 tricyclic systems were obtained, further enriching the diversity of 6/6/6 tricyclic systems (only one reported compound, 5, oxirapentyn To investigate the structure−activity relationship (SAR) of the anti-glioma activity, four new derivatives (10−13) were semisynthesized by making simple structural modifications (oxidation or hydrolysis) of the natural product oxirapentyn B (6) or oxirapentyn A (7) isolated from A. felina SYSU-MS7908 (Scheme 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These skeletons include 14 monocyclics (cyclohexene/ ane, e.g., iso-A82775C 40 ), 62 bicyclics {benzofuran (6/5, e.g., truncateols D−L 43 ), chromen (6/6, e.g., oxirapentyns F−J 31 ), naphthalene (6/6, biscognin B 44 ), and spiro[cyclohexene/anecyclopropane] (6/3, pestalotriols A and B 45 )}, 18 tricyclics {furo[2,3-g/h]chromene (5/6/6, e.g. pestalotheols A, B, and D 46 ), pyrano[2,3-g]chromene (6/6/6, oxirapentyn K 31 ), chromene−cyclocarbonate fused (6/6/5, biscognienyne F and felinoid A 30,44 ), cyclopropa[c]benzofuran (3/5/6, biscognienyne E 44 ), spiro[chromene-cyclopropane] (6/6/3, pestaloficiols B−E 47 ), and spiro[cyclopropane-naphthalene] (3/6/6, biscognin A 44 )}, and one tetracyclic {cyclopropa [3,4]furo[2,3h]chromene, 3/5/6/6, pestaloficiol A 47 }. In this study, four new members (1−4) with two distinct types of 6/6/6 tricyclic systems were obtained, further enriching the diversity of 6/6/6 tricyclic systems (only one reported compound, 5, oxirapentyn To investigate the structure−activity relationship (SAR) of the anti-glioma activity, four new derivatives (10−13) were semisynthesized by making simple structural modifications (oxidation or hydrolysis) of the natural product oxirapentyn B (6) or oxirapentyn A (7) isolated from A. felina SYSU-MS7908 (Scheme 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…During our ongoing search for bioactive natural products from fungi, 20–23 we isolated four new analogues of xyloketal B, simpliketals A–D ( 1–4 ), along with two other new compounds simplilactones A and B ( 5 and 6 ) from Simplicillium sp. AHK071-01 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…belongs to the Xylariaceae family, growing on the bark of trees and shrubs, preferably on dead or dying branches. Since the first report on the secondary metabolites in 2005 (Evidente et al, 2005), nearly 50 secondary metabolites have been reported, including azaphilones (Cheng et al, 2012), meroterpenoids (Zhao et al, 2017;Zhao et al, 2019;Zhao et al, 2021), sesquiterpenes (Amand et al, 2012), aromatics (Evidente et al, 2005;Cheng et al, 2012;Cheng et al, 2011), isocoumarins (Evidente et al, 2005;Cheng et al, 2012;Amand et al, 2012;Sritharan et al, 2019), amides (Cheng et al, 2012;Cheng et al, 2011), and cyclopeptides (Wu et al, 2016), which exhibit a widespread of bioactivities, including antimicrobial (Cheng et al, 2012), enzyme inhibitory (Wu et al, 2016), inhibitory of seed germination (Evidente et al, 2005), antiinflammatory (Zhao et al, 2021), or short-term memory enhancement in AD flies activities (Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous chemical investigation of a fungal strain of Biscogniauxia sp. (No.71-10-1-1), structurally diverse active meroterpenoids (diisoprenyl-cyclohexene/ane-type) and their dimers with new skeleton were identified (Zhao et al, 2017;Zhao et al, 2019;Zhao et al, 2021), which showed that this strain can produce natural products with rich chemical diversity. Further chemical investigation on this fungal strain was carried out, which led to the isolation of two new diterpenoids, including a seco-isopimarane type (1) and an abietane type (2).…”
Section: Introductionmentioning
confidence: 99%